Library online request for purchasing reading material system / Too Ser Ing - Too, Ser Ing (2002)
Library Online Request for Purchasing Reading Material System (LORS) is a web-based application where lecturers from University of Malaya (UM) can make their requisition for purchasing reading material to tile main library via the Internet. For the past few years, the requisition for purchasing reading materials has been done manually. Due to the inconvenience and time-consuming problems, it is worthy for us to develop a library online request service. The development of LORS is anticipated to include the use of Information Technology. LORS is mainly divided into 2 sections, which are user section and administrator section. User section is a web-based application, which implements the tasks of lecturer requisition on the web. While administrator section is a windows-based application, which performing the tasks of the administrator. The objectives of this project are to provide a convenient and user-friendly online request system, to provide easier database maintenance for administrator and to reduce processing error due to level of human intervention. This system's. modules have been designed on good and essential features identified from existing system available on the web. L RS hopes to meet the needs of both lecturers and administrators. They will be able to benefit from all the high-end features of this system. LORS is developed using Active Server Pages technologies and rapid application development (RAD) on the Microsoft 2000 Professional platform. It is aimed to have a high-performance back-end database that is Microsoft SQL Server 7.0 for providing accurate information.